Fault detection and fault‐tolerant control over signal‐to‐noise ratio constrained channels. (5th February 2018) - Guo, Fumin; Ren, Xuemei; Li, Zhijun; Han, Cunwu
Summary: This paper investigates the problems of fault detection (FD) and fault‐tolerant control for a class of discrete‐time systems with signal‐to‐noise ratio constrained channels. For the purpose of detecting the fault, an observer‐based FD scheme is proposed by using a descriptor system approach. In this scheme, an augmented robust FD filter is designed such that the residual generation system is admissible and the estimations of the system state and fault are both obtained; then, a dynamic threshold is constructed based on stochastic characteristics of the channel noise, a constant α is introduced to reduce the conservatism of threshold, and false alarm rate of the threshold is given. Subsequently, in order to keep the post‐fault system robust asymptotically stable, an output feedback fault‐tolerant control strategy is established on the basis of the fault estimation information. Finally, two simulation examples are provided to illustrate the effectiveness and feasibility of the proposed method.